Characterization of FDM 3D Printed Parts Using TPU + PETG Filaments For Shin Guard Products - Darsin, Mahros; Yulio, Agit Yoga; Syuhri, Ahmad; Ramadhan, Mochamad Edoward; W.C.S, I Made Ivan; Sumarji, Sumarji (Politeknik Negeri Lhokseumawe, 2024)
3D printing machines are used to print products that support sports activities, such as shin guards. During sports, shin guards are protective equipment to prevent injury to the lower legs. Filaments that are suitable for making shin guards are thermoplastic polyurethane (TPU) and polyethylene terephthalate (PETG) because they have impact resistance properties needed to protect the feet during sports. The variation is the level parameter layer height, nozzle temperature, printing speed, and bed temperature. Next, an impact test will be carried out to determine the optimal parameter variation on the 3D printing machine, which is expected to be a reference for printing quality products. This study uses a 3D printer, Ender v3, to print specimens and shin guard products. The material used is TPU+PETG filament. The Taguchi method with the orthogonal matrix L9(3)4 was repeated thrice for each experiment. After that, an analysis of variance was carried out. Parameter variations used in the study were layer height (0.1 mm, 0.2 mm, 0.3 mm), nozzle temperature (220℃, 225℃, 230℃), printing speed (45mm/s, 45mm/s, 50mm/s) and bed temperature. (70℃, 75℃, 80℃). In this study, Charpy impact testing will be carried out. The combination of factors that can produce an optimal impact test is layer height level 2 (0.2 mm), nozzle temperature level 1 (220℃), printing speed level 3 (50 mm/s) and bed temperature level 2 (75℃) with an impact strength value the highest was 27.20 and the lowest was 11.07. The combination of factors that have the most significant effect on the impact test strength values is layer height 63.97%, nozzle temperature 6.19%, printing speed 2.07% and bed temperature 4.74%.